2000
DOI: 10.1007/s003300050961
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstructed rotational digital subtraction angiography in planning treatment of intracranial aneurysms

Abstract: We evaluated three-dimensional (3D) reconstructions of 200 degrees rotational digital subtraction angiography (DSA) images for their contributions to improving the safety of endovascular embolization of intracranial aneurysms. Standard DSA and 200 degrees rotational DSA were performed in 40 adult patients (aged 21-77 years) with 45 intracranial aneurysms. Information obtainable from standard DSA and 3D-DSA images about aneurysm shape and size was compared. In 40 (89%) of the 45 aneurysms 3D-DSA gave additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 8 publications
0
48
0
Order By: Relevance
“…Volume rendering images of IV 3D DSA were more effective in demonstrating the relationship between the aneurysm and the adjacent vessels than MIP imaging. 6 For examination of the existence of small aneurysms and for analysis of the size of aneurysms and vessels, MIP produced from the original nonthreshold 3D data was feasible. 6 When data were transferred to the personal computer for reconstruction, the matrix size was transformed from 512 ϫ 512 to 256 ϫ 256 by voxel addition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Volume rendering images of IV 3D DSA were more effective in demonstrating the relationship between the aneurysm and the adjacent vessels than MIP imaging. 6 For examination of the existence of small aneurysms and for analysis of the size of aneurysms and vessels, MIP produced from the original nonthreshold 3D data was feasible. 6 When data were transferred to the personal computer for reconstruction, the matrix size was transformed from 512 ϫ 512 to 256 ϫ 256 by voxel addition.…”
Section: Discussionmentioning
confidence: 99%
“…6 For examination of the existence of small aneurysms and for analysis of the size of aneurysms and vessels, MIP produced from the original nonthreshold 3D data was feasible. 6 When data were transferred to the personal computer for reconstruction, the matrix size was transformed from 512 ϫ 512 to 256 ϫ 256 by voxel addition. This procedure is necessary for better contrast resolution because the contrast medium is diluted by a much larger volume of blood in IV 3D DSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers abroad showed the importance of 3D-DSA in the evaluation and the treatment of aneurysms [6][7][8].…”
Section: Researches Abroadmentioning
confidence: 99%
“…Compared with conventional two‐dimensional (2D) digital subtraction angiography, 3D CBRA provides more detailed information for the assessment of cerebral aneurysms and allows more exact depiction of anatomic details that are beneficial for interventional surgery 2 , 3 , 4 , 5 , 6 . Regarding the effective dose to the patient Bridcut et al (7) reported a mean total effective dose of 3.4 mSv for the assessment of aneurysms in a conventional coiling procedure.…”
Section: Introductionmentioning
confidence: 99%